Pemilihan Terapi Konservatif dan Operatif pada Endometriosis - cut rika maharani (Universitas Syiah Kuala, 2021)
Abstract. Abdominal pain during menstrual periods (dysmenorrhea), accompanied by pelvic pain, and infertility are symptoms that patients with endometriosis often complain of. Endometriosis is a chronic,inflammatory condition estrogen-dependent characterized by proliferation of the endometrial glands and stroma outside the uterine cavity. Endometriosis occurs in nearly 2-10% of women of childbearing age, 35-50% of women with pelvic pain or infertility. Incidence peaks at age 25-35 years, but is also at risk in young women with dysmenorrhea or pelvic pain. Women with endometriosis need management for pain, infertility or both. Treatment options depend on the age of the patient, the severity of clinical symptoms, the patient's fertility plan, previous management, and the location of the pain. Then It was adjusted to conservative or operative therapy based on the patient’s fertility plan.